The Effect of Government Expenditure in Education, Health, and Infrastructure on Poverty: A Panel Data Approach of Regencies/ Cities in North Sulawesi Province - Eva Nur Kumalasari (CV. Proaksara Global Transeduka, 2025)
Reducing poverty stands as a key objective in national development efforts. Governments have an essential function in lowering poverty rates by strategically distributing budget resources across critical areas including education, healthcare, and infrastructure development. This research examines how government spending in educational, healthcare, and infrastructure sectors influences poverty levels using panel data analysis from districts and municipalities in North Sulawesi Province between 2011 and 2020. The analysis employs a Random Effect Model methodology. The findings reveal that government investment in education and healthcare sectors significantly reduces poverty levels, whereas infrastructure spending paradoxically shows a significant positive correlation with poverty rates in North Sulawesi's districts and municipalities.